Perluasan Port-State Jurisdiction dalam EU ETS Sektor Pelayaran Berdasarkan Analisis UNCLOS 1982 - Nada Amira (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article examines the compatibility of the maritime EU Emissions Trading System (EU ETS) with the limits of port-state jurisdiction under UNCLOS 1982. The analysis focuses on the 50% emissions coverage for voyages between European Union ports and non-European Union ports, as this formula raises jurisdictional concerns where a substantial part of the emissions used as the basis of obligation occurs beyond EU jurisdiction. This research applies a normative legal method through statutory, conceptual and case approaches. The article finds that the EU ETS does not automatically violate UNCLOS 1982 because it maintains a jurisdictional nexus through port access. Nevertheless, the 50% formula problematically expands the prescriptive jurisdiction of port states because UNCLOS does not expressly authorize carbon obligations over part of an international voyage. The contribution of this article lies in clarifying the conceptual boundary between a valid port-entry condition and a potentially extraterritorial expansion of prescriptive jurisdiction. Therefore, the regulation of international shipping emissions should be directed toward stronger multilateral harmonization through the IMO to avoid fragmentation in the law of the sea.